2023
DOI: 10.3389/falgy.2023.1066392
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification by peroxynitrite enhances TLR4 activation of the grass pollen allergen Phl p 5

Abstract: The chemical modification of aeroallergens by reactive oxygen and nitrogen species (ROS/RNS) may contribute to the growing prevalence of respiratory allergies in industrialized countries. Post-translational modifications can alter the immunological properties of proteins, but the underlying mechanisms and effects are not well understood. In this study, we investigate the Toll-like receptor 4 (TLR4) activation of the major birch and grass pollen allergens Bet v 1 and Phl p 5, and how the physiological oxidant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Studies have shown that oxidative modifications can also alter the sensitisation of plant protein. In the study of betv 4 and Phlp4, birch and grass pollen allergens, researchers found that the physiological oxidant peroxynitrite forms protein dimers and higher oligomers through protein nitration, thereby enhancing the activation of toll‐like receptor 4, resulting in increased sensitivity to grass pollen allergen (Reinmuth‐Selzle et al ., 2023). Other studies have shown that plasma could cause oxidation of sesame protein, thereby reducing the binding ability of sesame protein to IgE antibodies (Unterhauser et al ., 2023).…”
Section: Effects Of Oxidation On the Physicochemical Properties And Q...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that oxidative modifications can also alter the sensitisation of plant protein. In the study of betv 4 and Phlp4, birch and grass pollen allergens, researchers found that the physiological oxidant peroxynitrite forms protein dimers and higher oligomers through protein nitration, thereby enhancing the activation of toll‐like receptor 4, resulting in increased sensitivity to grass pollen allergen (Reinmuth‐Selzle et al ., 2023). Other studies have shown that plasma could cause oxidation of sesame protein, thereby reducing the binding ability of sesame protein to IgE antibodies (Unterhauser et al ., 2023).…”
Section: Effects Of Oxidation On the Physicochemical Properties And Q...mentioning
confidence: 99%
“…In addition to its nutritional value, plant-based protein is also considered as functional ingredient and playing a variety of roles in food formulations, including thickener and gelling agents, stabilisers for emulsion and foam, and adhesives for lipid and water. It has been reported that the emulsion stability of beef sausages was improved after the addition of lupin protein (dos Santos et al, 2022). Moreover, faba bean protein powders have been used to make emulsion gels including yogurt and tofu analogues, while mung bean protein, due to its good hydrophobicity and antioxidant resistance, can form an adhesive film that acts as an excellent oxygen barrier (Hadidi et al, 2022;Zheng et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…However, dimer and trimer formation was observed but not quantified for the reaction of Bet v 1 with TNM ( 9 , 35 ). The reaction of Bet v 1 with ONOO yielded up to 42% protein dimers and higher oligomers ( 63 ). For Bet v 1, the tyrosine residues, Y5, Y66 and Y150 were suggested to be involved in the dityrosine cross-linking due to their solvent-exposed position ( 35 , 64 ).…”
Section: Dityrosine Cross-linkingmentioning
confidence: 99%
“…For Phl p 5, exposure to O /NO and ONOO lead to the formation of protein dimers and higher oligomers for up to 50% of the protein mass ( 30 , 63 ). For dimerization and further oligomerization, the effect of steric hindrance, however, is likely more important than for the nitration reaction ( 22 ).…”
Section: Dityrosine Cross-linkingmentioning
confidence: 99%
See 1 more Smart Citation